Economic feasibility study of expediency of establishment of solar modules in the private household - Shokarov, Dmitrо; Chorna, Viktoriia; Bogodist, Kseniia (НТУ "ХПІ", 2017)
The question of rather economic feasibility of use of solar modules in a private household as the power supply of household appliances is considered under the conditions of use of "a green tariff" in this article. The results of the calculations of the greatest possible volume of development of electric energy by solar modules for a year are given. On the basis of a method of discounting return on the investment in a photo-electric system is defined.

В роботі розглянуто питання щодо економічної доцільності застосування сонячних модулів в приватному домогосподарстві в якості джерела живлення побутових приладів та за умов використання "зеленого тарифу". Приведено результати розрахунків максимально можливого обсягу вироблення електричної енергії сонячними модулями протягом року. На основі метода дисконтування визначено окупність інвестицій у фотоелектричну систему.
Економічне обгрунтування встановлення сонячних модулей в приватному домогосподарстві
Keywords: rechargeable battery; green tariff; solar power; payback; efficiency; акумуляторна батарея; зелений тариф; сонячна енергетика